2004
DOI: 10.3201/eid1008.030840
|View full text |Cite
|
Sign up to set email alerts
|

Group G Streptococcal Bacteremia in Jerusalem

Abstract: Recurrent group G Steptococcus bacteremia, associated with lymphatic disorders and possibly emm stG 840.0, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
91
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 48 publications
15
91
2
Order By: Relevance
“…Fifty-two patients were men (53.6z), with a M:W gender ratio of 1.16:1. There was a higher prevalence of GGS than GCS, which agreed with a study from Denmark (4), and there were more adults than children in this study, which was also in agreement with a previous report (1).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Fifty-two patients were men (53.6z), with a M:W gender ratio of 1.16:1. There was a higher prevalence of GGS than GCS, which agreed with a study from Denmark (4), and there were more adults than children in this study, which was also in agreement with a previous report (1).…”
supporting
confidence: 93%
“…Group C and group G b-hemolytic streptococci (GCS/GGS) can cause severe infections, including bacteremia (1,2), and a broad spectrum of illnesses (e.g., pulmonary infections, arthritis, skin and soft tissue infections, endocarditis, urinary tract infections, and meningitis) (1,3). Increasing numbers of GGS infections have been reported in the USA (3) and Denmark (4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…equisimilis strains having group A antigen rather than group C or G antigen have also been reported (Bert & Lambert-Zechovsky, 1997;Brandt et al, 1999;Katsukawa et al, 2002). Many recent studies have reported that this organism causes invasive and systemic streptococcal infections like GAS (Natoli et al, 1996;Wagner et al, 1996; Hirose et al, 1997; Kugi et al, 1998;Barnham et al, 2002;Cohen-Poradosu et al, 2004;Hashikawa et al, 2004). The organism has also been reported to cause a wide variety of human infections such as pharyngitis, cellulitis, sepsis, meningitis and endocarditis (Woo et al, 2001).…”
Section: Introductionmentioning
confidence: 97%